Training on the use of video game learning media for clean and healthy living behavior for Aisyiyah kindergarten teachers, Surakarta City - Maryani Setyowati; Jaka Prasetya; Hesti Dina Apriyani; Sutrisno Sutrisno; Noor Alis Setiyadi (Universitas Muhammadiyah Magelang, 2021)
With the emergence of the Covid-19 pandemic at the end of 2019, Clean and Healthy Living Behavior (PHBS) is now more important than ever. This is inextricably linked to people's habits in maintaining their health, so that they are not exposed to Covid-19 disease. As information technology advances, so does the form of media used in learning. As a result, a video game about PHBS has been created to aid in learning and increase the knowledge of teachers at Aisyiyah Kindergarten in Surakarta City. The goal of this activity is to provide kindergarten teachers with training on how to use PHBS video games. This activity is carried out in stages, such as problem analysis, identifying teachers' characteristics, socializing about the use of interactive learning media, analyzing partner needs in interactive learning media, and training the use of PHBS video games. The activity resulted in an increase in PHBS knowledge as well as an increase in teachers' ability to use PHBS video games. The creation of PHBS video games is critical in order to assist teachers in providing PHBS material to their students.